Hostile intent and counter-terrorism : human factors theory and application - Stedmon, Alex; Lawson, Glyn (Ergonomist) (Human factors in defence., 2015)
"This volume brings together research from around the world to explore a range of topics within the project of detecting terrorist activities. It is divided into five key themes: conceptualising terrorism, deception and decision making, social and cultural factors in terrorism, strategies for counter-terrorism, and future directions. Twenty four chapters explore the spectrum of detecting terrorist activities, hostile intent, crowded public spaces and suspicious behavior. A variety of disciplines are represented, including ergonomics/human factors, psychology, criminology, cognitive science, sociology, political theory, engineering and computer science"--Provided by publisher